La trama dell'allegoria Scritture di ricerca e istanza allegorica nel secondo Novecento italiano - Caporiccio, Elisa (Biblioteca di Studi di Filologia Moderna, 2022)
The present study aims to examine the presence of allegory in literary works in prose, limiting the attention to a specific area of the second half of the twentieth century called 'letteratura di ricerca'. After discussing the most important theories about 'modern allegory', and particularly the debate that has developed in the Italian literary critic around the '80s, a series of textual analysis are gathered, focusing on several authors, such as Manganelli, Morselli, Volponi, Malerba, Arbasino, Sanguineti, Di Marco. As we can see from the exam of these works, narrative allegories have an impact both on the formal and the content-related level: the allegorical impulse can affect the structure of a novel, its formal aspects and its diegesis, as well as its relations with literary genres.